2022
DOI: 10.1021/acsbiomedchemau.2c00018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LipS1 and LipS2 from Thermococcus kodakarensis: Proteins Annotated as Biotin Synthases, which Together Catalyze Formation of the Lipoyl Cofactor

Abstract: Lipoic acid is an eight-carbon sulfur-containing biomolecule that functions primarily as a cofactor in several multienzyme complexes. It is biosynthesized as an attachment to a specific lysyl residue on one of the subunits of these multienzyme complexes. In Escherichia coli and many other organisms, this biosynthetic pathway involves two dedicated proteins: octanoyltransferase (LipB) and lipoyl synthase (LipA). LipB transfers an n-octanoyl chain from the octanoyl-acyl carrier protein to the target lysyl residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…33 A recent publication demonstrated that two enzymes from Thermococcus kodakarensis (LipS1 and LipS2), previously annotated as biotin synthases, have 4Fe−4S auxiliary clusters and work together to catalyze the formation of lipoyl groups on an octanoyl-lysyl-containing peptide substrate. 42 However, no current crystal structure for these enzymes exists, and Mossbauer spectroscopy data from this study cannot distinguish whether a sulfur atom is ligated to the 4Fe−4S auxiliary cluster. We believe that these novel lipoyl synthases will utilize a 4Fe−5S cluster as the sulfur source, similar to Type II BioBs.…”
Section: ■ Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…33 A recent publication demonstrated that two enzymes from Thermococcus kodakarensis (LipS1 and LipS2), previously annotated as biotin synthases, have 4Fe−4S auxiliary clusters and work together to catalyze the formation of lipoyl groups on an octanoyl-lysyl-containing peptide substrate. 42 However, no current crystal structure for these enzymes exists, and Mossbauer spectroscopy data from this study cannot distinguish whether a sulfur atom is ligated to the 4Fe−4S auxiliary cluster. We believe that these novel lipoyl synthases will utilize a 4Fe−5S cluster as the sulfur source, similar to Type II BioBs.…”
Section: ■ Discussionmentioning
confidence: 78%
“…This is based on the facts that LipS1 and LipS2 have an absolutely conserved His residue that is required for catalysis and a nearby hydrogen bond donor (serine) that are both structurally adjacent to the predicted binding site of the auxiliary 4Fe−4S cluster. 42 Due to this misannotation and the similarity between LipS1 and LipS2 with Type II BioB, this opens the possibility of an alternative substrate for boBioB. Since lipoate is mainly used for metabolism in aerobic organisms, many anaerobic bacteria do not contain a lipoyl synthase gene, 43 and as expected, there is no gene encoding for lipoyl synthase that can be found within published Blautia obeum genomes (NC_021022.1, NZ_CYZA01000015.1).…”
Section: ■ Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The work by Booker and colleagues showed that like the reaction catalyzed by Escherichia coli BioB, sulfur insertion takes place first at the terminal carbon of the substrate, while in canonical lipoyl synthases sulfur insertion takes place first at the internal (C6) carbon (Figure ). Unlike E. coli BioB, however, both LipS1 and LipS2 contain auxiliary [Fe 4 S 4 ] clusters …”
Section: Contributions To the Radical Sam Virtual Issue In Acs Bio An...mentioning
confidence: 99%
“…Unlike E. coli BioB, however, both LipS1 and LipS2 contain auxiliary [Fe 4 S 4 ] clusters. 63 One of the areas of RS enzymology that highlights the extreme power and versatility of these enzymes is in the generation of complex metallocofactors, such as the H-cluster of the [FeFe]-hydrogenase and the molybdenum−iron (MoFe) cofactor of nitrogenase (Figure 8). The [FeFe] hydrogenase is one of three subclasses of hydrogenases, which catalyze the reversible reduction of protons to H 2 .…”
Section: Issue In Acs Bio and Med Chem Aumentioning
confidence: 99%